2012
DOI: 10.1080/03067319.2012.663755
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive determination of Fenamiphos in water samples by flow injection photoinduced chemiluminescence

Abstract: In this work, a sensitive flow injection chemiluminescence (FI-CL) method for the determination of nematicide Fenamiphos in a rapid and simple way is proposed.Fenamiphos is firstly photodegraded in basic medium. These photofragments react with Ce(IV) providing the chemiluminescence signal. To the authors' knowledge, no chemiluminescence method has been described in the literature for the determination of the nematicide Fenamiphos. All physical and chemical parameters in the flow injection chemiluminescence sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…In fact, CL has been gaining increasing acceptance and has been used to determine OPPs residues in recent years [9][10][11][12][13][14][15]. Nevertheless, practical application of the HPLC-CL technique for the determination of pesticides is still uncommon.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, CL has been gaining increasing acceptance and has been used to determine OPPs residues in recent years [9][10][11][12][13][14][15]. Nevertheless, practical application of the HPLC-CL technique for the determination of pesticides is still uncommon.…”
Section: Introductionmentioning
confidence: 99%
“…The relative errors showed in both tables were obtained using 40 ng When the effect of other pesticides on the CL signal was tested, it was found that dimethoate, fenamiphos and methomyl showed a strong interfering effect. That result was expected, since an important CL response for the photoproducts of all of them when oxidized by cerium (IV) have been previously reported 21,[36][37] . Bearing in mind that fact, the use of a separative technique, such as LC, prior to analysis should be advisable when those pesticides are together with thiacloprid; thus, apart from their separation, their simultaneous determination should be achieved.…”
Section: Validationmentioning
confidence: 59%
“…A C C E P T E D ACCEPTED MANUSCRIPT 36 fungicides [159], bromoxynil [160], fenamiphos [161], norfloxacin [162], triclosan [163], diuron [164], vitamins A and C [165], 4-chloro-2-methylphenoxyacetic acid (MCPA) [166] and isoamyl nitrite [167] with LDs as low as 0.02 µmol L -1 .…”
Section: and Ion-exchange Cartridges) Later Applications Inclumentioning
confidence: 99%
“…photolithography and deep reactive ion etching [43]) are not promptly available in chemical labs, thus hindering the wide diffusion. In this sense, simpler and inexpensive approaches for production of microfluidic devices[32,161] or…”
mentioning
confidence: 99%